SHIFTING PARADIGMS: THE CHANGING DISCOURSE OF MEDICAL PRACTICES IN INDIA - Yadav, Suman (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Medicine is not merely a science but an art as well. It consists not merely of compounding mixtures, preparing decoctions, pills, plasters and drugs of all kinds but it also deals with the different processes of life. The practice of such medicines in India dealt not merely with the external body of man but also with the inner man or the soul since times immemorial. The science of medicine is of fundamental importance to keep our total mind and soul in harmony and peace. The history of medical science dates back to the history and evolution of a human civilizations. It prospered in all ancient civilizations of the world. The two major systems of medicine, which are ancient to the Indian soil, are the Siddha and the Ayurveda. The Siddha System of Medicine is the oldest and flourished in the South India, particularly in Tamil Nadu; and the Ayurveda was prevalent in North India. Later, with the arrival of the Muslim rulers in India, the Unani system of medicine, which is the direct outcome of the Graeco-Arabian medicine, was also introduced in India. All these systems of medicine are based on humoral pathology or, in other words, on the same physiological doctrine that air, bile (fire) and phlegm (water) are the three humours which maintain the human body through the combined functioning. The following pages elaborated these indigenous systems of medicine which still continue to be popular in India.